Cyberbullying and problematic internet use in adolescents with ADHD: exploring the relationship with moral disengagement and social skills - Sigal Eden; Tali Heiman; Dorit Olenik-Shemesh; Yaacov B. Yablon (Frontiers in Public Health)
This study explored the relationships between cyberbullying, problematic Internet use (PIU), moral disengagement, and social skills among children with and without Attention-Deficit/Hyperactivity Disorder (ADHD) due to the scarcity of research in this domain. The sample comprised 3,021 children aged 9–18 (M = 13.74; SD = 3.09), categorized into two groups: 2,247 (74.4%) typically developed (TD) children and 774 (25.6%) diagnosed with ADHD. Participants completed eight questionnaires assessing the study’s variables. Results revealed that children with ADHD displayed higher Internet use, greater PIU, and increased susceptibility to cyberbullying compared to TD peers, alongside elevated moral disengagement and lower social skills. Across both groups, heightened moral disengagement correlated with increased cyberbullying and PIU, while stronger social skills predicted reduced victimization, perpetration, and lower PIU. Moral disengagement emerged as a key factor influencing cyberbullying and PIU in both groups. These findings highlight the heightened risks for children with ADHD and provide insight for developing tailored interventions to address these challenges.